2004
DOI: 10.1007/s10350-004-0694-9
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Controlled Multicenter Trial Comparing Stapled Hemorrhoidopexy and Ferguson Hemorrhoidectomy: Perioperative and One-Year Results

Abstract: These data demonstrate that stapled hemorrhoidopexy offers the benefits of less postoperative pain, less requirement for analgesics, and less pain at first bowel movement, while providing similar control of symptoms and need for additional hemorrhoid treatment at one-year follow-up from surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
217
2
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(239 citation statements)
references
References 24 publications
9
217
2
11
Order By: Relevance
“…Additionally, SH procedure also resulted in shorter hospital stay, early recovery, and time to resume normal activities. The other studies also have reported shorter hospital stay post SH procedure [18][19][20][21][22]. Our case series also showed similar findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, SH procedure also resulted in shorter hospital stay, early recovery, and time to resume normal activities. The other studies also have reported shorter hospital stay post SH procedure [18][19][20][21][22]. Our case series also showed similar findings.…”
Section: Discussionsupporting
confidence: 90%
“…The complication rate reported in this study varies from 1% to 15% and lesser as compared to other studies (6-32%) [20,[24][25][26][27][28][29]. Post operative bleeding leading to interventions is reported 6-8 % in these studies as compared to 1.05% in our study.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The clinical effectiveness have been proved by showing minimal post-operative pain, shorter hospital stay, early to resume the work, shorter operative time, and acceptable safety profile [10][11][12][13][14][15][16]. Many of the studies [18][19][20][21][22] reported the average length of operation time was around 25 minutes, highlighting the saving time as compared to conventional surgeries. Additionally, SH procedure also resulted in shorter hospital stay, early recovery, and time to resume normal activities.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis comparing stapled hemorrhoidopexy and open hemorrhoidectomy, incidence of urinary retention was similar [54]. The expected reduction of postoperative urinary retention after stapled hemorrhoidopexy, caused by less postoperative pain, was not confirmed in the study by Senagore et al [55], which showed that pain was not a risk factor for urinary retention.…”
Section: Complicationsmentioning
confidence: 94%